2019
DOI: 10.1002/rcm.8353
|View full text |Cite
|
Sign up to set email alerts
|

Study of the mainstream cigarette smoke aerosols by Fourier transform ion cyclotron resonance mass spectrometry coupled to laser/desorption and electrospray ionization – Additional insights on the heteroaromatic components

Abstract: Rationale:The chemical composition of the particulate phase of cigarette smoke inhaled by the active smoker is still poorly known in spite of its importance from a health point of view. A non-targeted approach is applied to cigarette smoke particles collected on a quartz filter to obtain an as complete as possible description of this complex mixture.Methods: A home-made smoking machine including devices for volatile organic compounds (VOCs) and particle sampling was used. The validation of the cigarette smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…First, there are an estimated 8700 chemicals reported to be present in tobacco smoke [ 18 , 99 , 100 ], and the current study has only screened 34 chemicals identified as highly concentrated. Moreover, there are several tobacco smoke chemicals that are present in the gaseous state, are highly volatile, or lack protons, and thus are not detectable by NMR [ 18 , 21 , 99 , 101 , 102 , 103 , 104 , 105 , 106 ]. Second, there are likely toxic chemicals in CSC found within the low µM or nM concentration that were not detectable because of the sensitivity of NMR.…”
Section: Discussionmentioning
confidence: 99%
“…First, there are an estimated 8700 chemicals reported to be present in tobacco smoke [ 18 , 99 , 100 ], and the current study has only screened 34 chemicals identified as highly concentrated. Moreover, there are several tobacco smoke chemicals that are present in the gaseous state, are highly volatile, or lack protons, and thus are not detectable by NMR [ 18 , 21 , 99 , 101 , 102 , 103 , 104 , 105 , 106 ]. Second, there are likely toxic chemicals in CSC found within the low µM or nM concentration that were not detectable because of the sensitivity of NMR.…”
Section: Discussionmentioning
confidence: 99%
“…FTIR-MS in combination with LDI allows less sample preparation; however, it is amenable mainly to ionizing aromatic hydrocarbons. Therefore, to expand the range of detectable analytes, particularly polar compounds that may not be efficiently ionized by LDI, ESI was incorporated into the analytical approach . Also, nuclear magnetic resonance (NMR) spectroscopy has been utilized to profile the chemical composition of cigarette smoke condensate .…”
Section: Resultsmentioning
confidence: 99%
“…Even though the number of compounds in commercially available libraries for GC- and LC-MS (MS/MS, HRMS) has greatly increased in recent times more work still needs to be done to improve the spectral databases for improved compound identification. ,, Furthermore, alternative techniques such as in silico or de novo identification can be further explored to improve the detection of unknown compounds. , In addition, the difference in ionization methods used during spectral library build-up and experimental spectra generation often results in low matching factors during compound identification. , Because of this, there is no standard threshold value for the match factor used for tentative compound identification, and wide variations are in use among different researchers. This variability makes it difficult to compare interlaboratory results. Also, issues with distinguishing between isomers during peak identification have been reported . Similarly, compound identification for NTA using NMR spectroscopy is also challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they have been detected in exhaled breath [ 30 ], especially they were reported as lung cancer markers in exhaled breath in a series of papers [ 31–34 ]. But many aromatic VOCs were also reported as results of cigarettes exposure [ 35 ], which made it doubtful whether they can be available lung cancer markers. In our view, even cigarette smoke may be the source of these molecules, their levels still make sense.…”
Section: Discussionmentioning
confidence: 99%